Restricted Intimal Ca2+ Signaling Associated With Cardiovascular Disease - Taylor, Mark S.; Lowery, Jordan; Choi, Chung-Sik; Francis, Michael (Frontiers in Physiology, 2022)
Endothelial dysfunction is a key feature of cardiovascular disease (CVD) including atherosclerosis. Impaired endothelial signaling leads to plaque formation, vascular wall remodeling and widespread cardiovascular dysregulation. The specific changes along the vascular intima associated with atherosclerosis, including the vulnerable circulation downstream of the flow obstruction, remain poorly understood. Previous findings from animal models suggest that preservation of a distinct Ca2+ signaling profile along the arterial endothelial network is crucial for maintaining vasculature homeostasis and preventing arterial disease. Ca2+ signaling in the intact human artery intima has not been well characterized. Here, we employed confocal imaging and a custom analysis algorithm to assess the spatially and temporally dynamic Ca2+ signaling profiles of human peripheral arteries isolated from the amputated legs of patients with advanced CVD (peripheral artery disease and/or diabetes) or patients who had lost limbs due to non-cardiovascular trauma. In all tibial artery branches (0.5–5 mm diameter) assessed, the intima consistently elicited a broad range of basal Ca2+ signals ranging from isolated focal transients to broad waves. Arteries from patients with existing CVD displayed a restricted intimal Ca2+ signaling pattern characterized by diminished event amplitude and area. Stimulation of type-4 vanilloid transient receptor potential channels (TRPV4) amplified endothelial Ca2+ signals; however, these signals remained smaller and spatially confined in arteries from patients with CVD verses those without CVD. Our findings reveal a characteristic underlying basal Ca2+ signaling pattern within the intima of human peripheral arteries and suggest a distinct truncation of the inherent Ca2+ profile with CVD.